TEORI EVOLUSI ASAL USUL MAKHLUK HIDUP DAN ASAL USUL MANUSIA BERDASARKAN PERKEMBANGAN BIDANG GENETIKA MOLEKULER (BEBERAPA PEMIKIRAN PEMBELAJARAN TEORI EVOLUSI DI SEKOLAH) - Nusantari, Elya (Sainstek, 2006)
Human being evolution development, firstly started by many postulates and develop through Darwin evolution theory. The next development pointed out by focil findings and finaly shape human being evolution tree. Moleculer genetics development revealed how evolution concept develope. Firstly, evolution was a simple human being changing to be a complex human being. Through molecular genetics findings, evolution was genetic changing from human life to adaptive situation. The definition of evolution tree was not based on morfologys . But based on DNA analysis, namely tRNA and rRNA. Learning evolution theory at school need critical analysis in relation with development of material and sciens. It is needed spesific curriculum about human being origin.